SYNTHESIS OF SILVER NANOPARTICLES FROM LANNEA ACIDA VIA AQUEOUS AND METHANOLIC LEAF EXTRACT (FUDMA JOURNAL OF SCIENCES, 2024)
The reducing ability of plant extract cost-effectiveness is the major factor to consider in the green synthesis of metal nanoparticles. The present study investigates two different extraction methods for the green synthesis of silver nanoparticles (AgNPs) via aqueous and methanolic Lannea acida leaf extract for the first time. The effect of silver nitrate concentration, and quantity of the silver nitrate (volume) on that of plant extract and studied by UV–Vis spectroscopy and Fourier-transform infrared (FT-IR) spectroscopy. The methanolic extract silver nanoparticles show a remarkable difference compared to silver nanoparticles synthesized from the aqueous extract, this is ascertained that methanol has the potential applications than the silver nanoparticles synthesized from aqueous extract.
Keywords: Silver nanoparticles; Green synthesis; Extraction methods; Lannea acida; UV–Vis spectroscopy